A visual scale to rate amygdalar atrophy on MRI - Pizzini, Francesca B.; Ribaldi, Federica; Natale, Valerio; Scheffler, Max; Rossi, Vittoria; Frisoni, Giovanni B. (European radiology, 2025)
Background Visual rating scales are routinely used in clinical radiology to assess brain atrophy on scans of patients with suspected neurodegenerative conditions. Limbic predominant age-related TDP-43 encephalopathy (LATE) has recently been described, featuring early and severe atrophy of the amygdala. However, there is currently no scoring system specifically designed to assess amygdalar atrophy on MRI. Objectives to develop and validate a visual rating scale for amygdalar atrophy. Materials and methods Stringent criteria were developed for no, mild/moderate, and severe amygdalar atrophy based on axial and coronal volumetric T1-weighted MRI scans. Inter- and intra-rater reliabilities were estimated by three independent expert neuroradiologists in 100 randomly selected scans from the Geneva Memory Center cohort selected to be representative of the variability of medial temporal atrophy. Convergent validity was evaluated versus amygdalar volumes extracted by FreeSurfer on 1943 consecutive patients. Criterion validity versus autopsy-confirmed LATE neuropathologic changes were studied in the pathological subset of the Alzheimer’s Disease Neuroimaging Initiative (ADNI) cohort ( N = 96). Results Intra- and inter-rater agreements of amygdalar visual ratings were between substantial and almost perfect (weighted Cohen’s Kappa 0.71 to 0.93). Visual ratings were strongly associated with amygdalar volumes ( p ≤ 0.001 on the Kruskal–Wallis test). LATE neuropathologic changes were associated with visual ratings of amygdalar atrophy ( p = 0.057 on a test for trend). Conclusion The proposed visual amygdalar atrophy scale is a reliable and valid tool to assess amygdalar atrophy on MRI and can be a useful adjunct in routine radiological reporting. Key Points Question Assessment of amygdalar atrophy is crucial for diagnosing neurodegenerative diseases, as the limbic predominant age-related TDP-43 encephalopathy, yet no validated visual rating scale exists. Findings The proposed amygdalar atrophy scale demonstrated high intra-rater and inter-rater reliability, strong correlation with amygdalar volumetry, and association with limbic predominant age-related TDP-43 encephalopathy (LATE). Clinical relevance The amygdalar atrophy scale provides a reliable practical assessment tool that enhances diagnostic accuracy for dementia-related conditions, particularly aiding in identifying limbic predominant age-related TDP-43 encephalopathy.